2016
DOI: 10.1021/acs.chemmater.5b04398
|View full text |Cite
|
Sign up to set email alerts
|

Unambiguous and Controlled One-Pot Synthesis of Multifunctional Silica Nanoparticles

Abstract: Existing strategies for the synthesis of functional silica nanoparticles (SiNPs) rely on surface modifications followed by grafting of the organic moiety via chemoselective chemistry. Under these conditions, the introduction of several elements (e.g., ligands, drugs, fluorophores, vectors, etc.) on the same particle in a desired ratio and density is particularly difficult to achieve. We developed a method for obtaining in a single step well-defined tunable multifunctional fluorescent particles, presenting at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The fluorescein-labeled silane triethoxysilyl fluorescein was incorporated into SiPs at a ratio of 1 to 20 to the R5 peptide. 15 Similarly, a progressive uptake was observed that led to accumulation of the fluorescent SiPs in the cytoplasm of HT-29 cells after 3 h (Fig. 2C and D).…”
supporting
confidence: 54%
“…The fluorescein-labeled silane triethoxysilyl fluorescein was incorporated into SiPs at a ratio of 1 to 20 to the R5 peptide. 15 Similarly, a progressive uptake was observed that led to accumulation of the fluorescent SiPs in the cytoplasm of HT-29 cells after 3 h (Fig. 2C and D).…”
supporting
confidence: 54%
“…In numerous studies, covalent conjugation of organic dyes with MSNs has been suggested as the simplest chemical approach to provide fluorescent imaging modality. The organic dyes can be conjugated either on the surface of mesopores (Ciccione et al, ; Heidegger et al, ; Pan, Liu, He, Wang, & Shi, ) or in the silica matrix (Ahn, Park, Singha, Park, & Kim, ; Huang et al, ; Liong et al, ; Lu, Liong, Li, Zink, & Tamanoi, ; Lu, Wu, Hung, & Mou, ; Slowing, Trewyn, & Lin, ). For the surface conjugation, the chemical modification of the intrinsic silanol groups on the mesopore surface provides an active reaction site for covalent conjugation of the dye molecules.…”
Section: Msns Conjugated With Organic Dyesmentioning
confidence: 99%
“…125 The chemoselectivity of the sol-gel process was also exploited to propose a modular strategy leading to functional hybrid hydrogels (Class II.d, Figure 22) from a bis-silylated building block (e.g. PEG) used for the network establishment, and other alkoxysilane hybrid precursors 148 (e.g. silylated dyes, silylated integrin ligands for cell adhesion and silylated antibacterial peptides).…”
Section: Nanostructured Hydrogels As Biomaterialsmentioning
confidence: 99%